African indigenous knowledge system as a catalyst for enriching Nigeria's music education programme (2017)
The uniqueness of African indigenous knowledge systems (IKS) and the benefits of integrating them into Africa’s music educational programme were some of the issues that occupied the front burner at the birth of the Pan African Society for Musical Arts Education (PASMAE). It represented one of the responses to the wake up call to Africa to look inward in search of truly African sensitive and African-oriented solutions to a myriad of her music educational challenges in the world that is changing with bewildering speed. This paper x-rays the contents of music programmes in Nigeria’s tertiary institutions with a view to identifying IKS elements contained in them. Using observation and a checklist of curriculum implementation of Nigeria’s leading music technology programme as methodology, the paper highlights challenges confronting implementers in realizing set objectives. Findings confirm that the abundant richness of Africa’s IKS is yet to be harnessed. The paper concludes by making specific recommendations on how various stakeholders, including the Department of Music Technology, the Polytechnic, Ibadan, can innovatively achieve the much-desired goal of standardization, fabrication, massive production and promotion of traditional musical instruments to facilitate practical teaching.